Sistem Monitoring Evaluasi Pendekatan Sistem Pendidikan - Makmur Syukri; Fachruddin Fachruddin; Nuzurul Harmuliani; Rubino Rubino; Ade Putra (Jurnal Dirosah Islamiyah, 2023)
The purpose of this research is to find out the monitoring and evaluation system of the education system approach. The process of monitoring the implementation of subordinate work is carried out to obtain facts, data and information in the process of efforts to achieve goals, whether in accordance with predetermined standards and no deviations occur. Monitoring requires leaders to directly see the process that occurs, as well as with the support of documents and opinions from those being monitored, this is done as validation and validity of the monitoring process. The system approach is a way to identify needs, select problems, compile identification of problem solution requirements, create several alternative solutions, evaluate the results of revising requirements on part or all systems related to limitations in meeting needs. Education as an open system, really requires a systems approach in its development. Because, with the open system, education will always try to update itself so that it remains relevant and not outdated. The risk of this open system is that education will always encounter problems every time changes are made, so it requires a robust system approach to find a solution. Keywords: Monitoring Evaluation, Education System Approach